A dinâmica econômica da indústria química e farmacêutica durante o século XX nos EUA e Europa - João Paulo Borges Lisboa (2012)
Technological innovation is central in explaining the economic dynamics in the neo- Schumpeterian theory constitutes the primary source, is the expansion and dynamism of the economic system, is the generation and maintenance of asymmetries between companies or countries. The basic agent of the firm's competitiveness, it is this that take crucial investment decisions (concerning not only the intensity but also its orientation) and is in its interior that create, maintain and extend different skills. Economic theory points to the innovative activity as a form of growth and development of a company, a sector or an industry. In the course of the Industrial Revolution we find that the growing need for new technologies has become a common demand of any nation or industry that wanted to expand their profits. We can see that, since 1870, cemented a new wave of technology called the Second Industrial Revolution in which the chemical and pharmaceutical industries stand out from other industries for its high level of investment in R & D. The thesis presents the dynamics of chemical and pharmaceutical industry inthe United States and Europe during the twentieth century, according to Alfred Dupont Chandler, Jr. By the end of World War II, the chemical and pharmaceutical industries were transformed and began to market a new learning, from the petrochemical and the antibiotic revolution respectively. But in the 1970s, the chemistry has provided no new learning required for the commercialization of new products, although some drugs haveemerged in the pharmaceutical industry. In the 1980s, large pharmaceutical companies, including Eli Lilly, Merck and Schering Plough to commercialize the first products of biotechnology, and the twenty-first century, the infrastructure of this biotechnology revolution was comparable to the second industrial revolution, just before the FirstWorld War and the information revolution in 1960. Shaping the Industrial Century is an important contribution to our understanding of the most dynamic industries in the modern era. Alfred Chandler argues that only with consistent attention to R & D and an emphasis on long-term strategies a company can succeed over time. He details thesechemical processes for nearly every major pharmaceutical firm, demonstrating why some companies forged ahead while others do not.